PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN TRADISI MITONI DIKAMPUNG BUNGARAYA KECAMATAN BUNGARAYA KABUPATEN SIAK - Suntari, Suntari; Erlinda, Sri; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: This research is motivated to explain the people's perceptions of the implementation of the mitoni tradition and the meaning contained in the implementation of this mitoni tradition in Kampung Bungaraya. The formulation of the problem of this research is